2005
DOI: 10.1111/j.0014-3820.2005.tb01810.x
|View full text |Cite
|
Sign up to set email alerts
|

Local Adaptation to Winter Conditions in a Passerine Spreading North: A Common-Garden Approach

Abstract: Abstract. Sedentary passerine birds living in temperate and boreal regions need a high metabolic capacity for thermogenesis to survive winter conditions. As a consequence of the increased thermogenic capacity, basal energetic demands rise at a time when resources and time to acquire them decrease. In a previous study, great tits (Parus major) from two localities in Fennoscandia with contrasting winter conditions differed in their metabolic response to ambient temperature. To investigate the physiological basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 35 publications
4
62
0
Order By: Relevance
“…These observations are consistent with Weathers' [14]'s finding that avian BMR increases with increasing latitude, Wiersma et al's [12] observation that tropical birds have lower BMRs than their temperate counterparts, as well as with the negative correlation between temperature and BMR in mammals [10]. A negative effect of Temp avg on avian BMR has also been demonstrated to explain intraspecific variation [16], [56]. Moreover, numerous studies of thermal acclimation or acclimatization have found that birds adjust BMR in response to changing thermoregulatory demands [21][23], [25], [50], [57], [58].…”
Section: Discussionsupporting
confidence: 84%
“…These observations are consistent with Weathers' [14]'s finding that avian BMR increases with increasing latitude, Wiersma et al's [12] observation that tropical birds have lower BMRs than their temperate counterparts, as well as with the negative correlation between temperature and BMR in mammals [10]. A negative effect of Temp avg on avian BMR has also been demonstrated to explain intraspecific variation [16], [56]. Moreover, numerous studies of thermal acclimation or acclimatization have found that birds adjust BMR in response to changing thermoregulatory demands [21][23], [25], [50], [57], [58].…”
Section: Discussionsupporting
confidence: 84%
“…Thus, BMR was measured in terms of oxygen consumption during the night in an open-circuit respirometer in a dark climate cabinet at a constant temperature of 25°C, which is within the thermoneutral zone for winter acclimatized great tits (own unpublished data). Both the respirometer and data extraction procedures have been described in detail in previous studies (Broggi et al 2004(Broggi et al , 2005. After one night of measurements, birds were released at the location of capture.…”
Section: Metabolic Measurementsmentioning
confidence: 99%
“…Our main analysis concerns the great tit population in Oulu, northern Finland but also some data from a population close to Lund, southern Sweden is analyzed. Furthermore, as these two populations have intrinsic differences in their BMR level (Broggi et al 2004(Broggi et al , 2005, we predict that the rate of a possible age-dependent decline in BMR should differ between the two populations.…”
Section: Introductionmentioning
confidence: 98%
“…Garant et al (2005) discovered that the mean fledgling mass (and breeding value) of great tits decreased in one part of Wytham woods. A significant genetic component to variation in these fitness or fitnesslinked traits was documented in both studies (see also Broggi et al, 2005). These findings were possible because of intensive demographic studies, with populations studied for up to 35 years, detailed pedigrees and the ability to mark, recapture and measure hundreds of individuals.…”
Section: Neutral Versus Fitness Traits In the Great Titmentioning
confidence: 67%